Zinc‐Oxynitride TFTs: Toward a New High‐Mobility Low‐Cost Thin‐Film Semiconductor. Issue 2 (1st March 2013) - Ye, Yan
Abstract : Demands for high‐performance, low‐cost, and low‐energy‐consumption displays continue to drive the development of new semiconductor materials. The success of the metal‐oxide semiconductor IGZO for display backplanes has triggered even more activity, and zinc oxynitride is proposed as a possible solution.